2014
DOI: 10.1007/s40615-014-0037-z
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Competing Activities and Sleep Problems in Minority College Students

Abstract: This study addressed health disparities in sleep duration, sleep quality, and daytime sleepiness among African-American college students. To investigate evening behaviors promoting insufficient and inadequate sleep, we assessed electronic (e.g., computer and music) and nonelectronic (e.g., socializing) sleep competing activities (SCA). Students (N=154) were recruited from a Historically Black College (HBCU). The results showed more dysfunction than has previously been reported in college populations, with HBCU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
6
1
3
Order By: Relevance
“…15 This 12-item questionnaire assesses the impact of behaviors that may influence sleep in adolescents (e.g. : how many times a week do you play video-games after bedtime, how many times a week do you read, study, or do homework after bedtime).…”
Section: Methodsmentioning
confidence: 99%
“…15 This 12-item questionnaire assesses the impact of behaviors that may influence sleep in adolescents (e.g. : how many times a week do you play video-games after bedtime, how many times a week do you read, study, or do homework after bedtime).…”
Section: Methodsmentioning
confidence: 99%
“…For example, one study found that over 60% of college students are categorized as poor sleepers, with 70.6% obtaining less than 8 hr of sleep per night (Lund, Reider, Whiting, & Prichard, 2010). These sleep outcomes may disproportionally impact Black college students, with 62% reporting very short sleep durations (≤6.5 hr), 61% reporting high levels of daytime sleepiness, and 63% reporting poor sleep quality (Billings & Berg-Cross, 2014).…”
Section: Black-white Disparities In Sleepmentioning
confidence: 99%
“…Panašūs rezultatai nustatyti 2014 m. tyrime: 63 proc. afroamerikiečių studentų skundėsi bloga miego kokybe [7]. Geresni rezultatai gauti 2014 m. atliktame tyrime Kinijoje.…”
Section: įVadasunclassified
“…Amerikiečių autorių tyrimai rodo, kad bloga miego kokybė nustatyta 63 proc. afroamerikiečių studentų [7]. Šie rezultatai panašūs į mūsų ir kitų Lietuvos tyrėjų pateikiamus rezultatus.…”
Section: Rezultatų Aptarimasunclassified